A new approach to enter Retzius space in laparoscopic transabdominal preperitoneal bilateral inguinal hernia repair - Lifei Tian; Le Zhang; Zeyu Li; Likun Yan; Xiaoqiang Wang (BMC Surgery, 2023)
Abstract Background To investigate the feasibility, safety and efficacy of the right-side approach to enter Retzius space in laparoscopic transabdominal preperitoneal bilateral inguinal hernia repair. Methods Retrospective analysis was performed on 189 patients who were diagnosed with bilateral inguinal hernia preoperatively or intraoperatively and underwent selective TAPP in the General Surgery I Section of Shaanxi Provincial People’s Hospital from January 2015 to September 2020. 94 cases were performed using the right-side approach (research group), and 95 cases with conventional approach (control group). Intraoperative and postoperative conditions of the two groups were observed and compared. Results All operation were completed successfully. The operative time of research group was significantly shorter than that of control group (128.8 ± 35.4 vs 144.1 ± 40.9 min, P = 0.006). There were no significant differences in postoperative hospital stay, VAS score on first postoperative day, incidence of seroma and hematoma, urinary retention and other complications (P > 0.05). None of the patients occured hernia recurrence, mesh infection, intestinal obstruction and other complications. Conclusions The right-side approach to enter Retzius space is safe and feasible in TAPP surgery of bilateral inguinal hernia. Compared with the conventional approach, it can shorten the operative time and has certain advantages.